EFFECTIVENESS OF ANTIHELMINTIC MEDICINES IN THE TREATMENT OF FASCIOLYSIS IN GOATS IN THE CONDITIONS OF SURKHANDARDO REGION - Togaymuradov Mansur Salomatovich; T. I.Taylakov; Kudratova Marjona Bahrom qizi (Web of Journals Publishing, 2025)
The prevalence, extensiveness, and intensity of fascioliasis among goats in the Surkhandarya region have been determined
Keywords: Fasciola hepatica, Fasciola gigantica bioekologiya, trematod, gelmint, geksaxloretan, geksaxlorparaksilol, geksixol, bitionol, sulfen, diamfenetid, zanil, fazineks, doveniks, rafoksanid, dertil, albendazol, alben, rolenol.